A little love - Hamilton, Virginia, 1936-2002. (New York : Philomel Books, 1984)
Though she has been raised lovingly by her grandparents, an African-American teenager goes in search of her father.
Booklist starred.
Notable/Best Books (A.L.A.).
Wilson's Senior High School.
6.8
6.8
7-10.
Keywords: African Americans -- Fiction; African Americans -- Fiction